The Effect of Implementing the Problem Posing Learning Model on the Self-Efficacy Ability of High School Students - Siswanto, Deny Hadi; Kintoko; Rambe, Muhammad Yusuf; Mutmainah, Siti (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to analyze the effect of implementing the Problem Posing learning model on students' self-efficacy. A quasi-experimental method with a nonequivalent post-test only control group design was used. The research subjects were 11th-grade science students at Muhammadiyah Mlati Senior High School, selected using purposive sampling. Data were collected through tests, questionnaires, and observations. The instruments consisted of post-test questions to assess self-efficacy and observation sheets to evaluate teacher activities. Data analysis used a two-way ANOVA technique. The results showed a significance value of 0.000, which is less than the 0.05 significance level. This indicates that the regression coefficient is statistically significant, and the H0 was rejected. These findings suggest that the Problem Posing learning model significantly affects students’ self-efficacy. The model contributes to 85.6% of the observed increase in students' self-efficacy. Therefore, it can be concluded that the implementation of the Problem Posing learning model plays an important role in enhancing students’ confidence in their academic abilities, making it a potentially effective instructional strategy in science education.